(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The homogeneous third degree equation with four unknowns represented by the Diophantine equation = is considered for its patterns of non – zero integral solutions. A few fascinating properties among the solutions and special integer are presented.